The International Vitreoretinal B-Cell Lymphoma Registry: a protocol paper - David J Wilson; Valérie Touitou; Justine R Smith; Manabu Mochizuki; Hiroshi Takase; Steven Yeh; Alexandra L Farrall; H Nida Sen; Daniel V Vasconcelos-Santos; Joke H de Boer; Ninette H ten Dam-van Loon; Janet L Davis; et al. (BMJ Open)
Introduction Vitreoretinal lymphoma is a rare ocular cancer with high morbidity and mortality despite treatment. Diagnosis by cytopathology is often delayed, and various molecular and image-based investigations have been developed. Diverse treatments are used, but there is a limited medical evidence to differentiate their effectiveness. We designed an international registry that would collect diagnostic, treatment and outcomes data, to establish new evidence for the management of this cancer.Methods and analysis The International Vitreoretinal B-Cell Lymphoma Registry will accrue data retrospectively for individuals aged 18 years or older, diagnosed with new or recurrent vitreoretinal B-cell lymphoma on or after 1 January 2020. A steering committee of subspecialised ophthalmologists identified 20 key clinical data items that describe patient demographics, tissue involvements, diagnostic testing, ocular and systemic treatments and treatment complications, and visual acuity and survival outcomes. Customised software was designed to permit collection of these data across a single baseline and multiple follow-up forms. The platform collects data without identifiers and at 3 month reporting intervals. Outcomes of the project will include: (1) descriptions of clinical presentations, and diagnostic and therapeutic preferences; (2) associations between clinical presentations, and diagnostics and treatments, and between diagnostics and treatments (assessed by ORs with 95% CIs); and (3) estimations of rates of vision loss, and progression-free and overall survival (assessed by Kaplan-Meier estimates).Ethics and dissemination The registry has received Australia-wide approval by a national human research ethics committee. Sites located outside Australia are required to seek local human research ethics review. Results generated through the registry will be disseminated primarily by peer-reviewed publications that are expected to inform clinical practice, as well as educational materials.